Forced vital capacity predicts morbidity and mortality in adult patients with Fontan circulation. (September 2017) - Cohen, Katie E.; Buelow, Matthew; Dixon, Jennifer; Brazauskas, Ruta; Cohen, Scott; Earing, Michael G.; Ginde, Salil
Highlights: Abnormal lung function is common after the Fontan operation. Reduced forced vital capacity predicts clinical outcomes after the Fontan operation. Older age at time of Fontan is associated with lower forced vital capacity.